2006
DOI: 10.2345/i0899-8205-40-2-150.1
|View full text |Cite
|
Sign up to set email alerts
|

A Prototype Infant Incubator for Heliox Therapy

Abstract: Heliox (Hx) gas has been shown to improve pulmonary function in infants, but methods for its delivery are invasive and problematic. To this end, we modified an Isolette (Hill-Rom Air-Shields) infant incubator (Hxl) to deliver Hx respiratory gas mixtures noninvasively while providing thermal stability for neonatal care in the Neonatal Intensive Care Unit (NICU). In vitro tests and in vivo animal studies were performed to compare the original design specifications and established baseline performance criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…2 Since then, incubators have evolved into modern devices with increased capabilities, such as heliox 9 and computerized environmental control. Despite the improvements in design and technology of incubators, opening a side access door or handports can lead to heat and humidity loss.…”
Section: Introductionmentioning
confidence: 99%
“…2 Since then, incubators have evolved into modern devices with increased capabilities, such as heliox 9 and computerized environmental control. Despite the improvements in design and technology of incubators, opening a side access door or handports can lead to heat and humidity loss.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ensuring that the infant is maintained in a thermoneutral environment may assist in the respiratory therapy by minimizing oxygen requirements. Measurement of the central temperature (rectal, esophageal) with thermistor or thermocouple sensors can be carried out, although this is generally not done; instead, reliance is placed on the use of an abdominal mounted skin surface sensor that is part of the incubator or warmer servocontrol system.…”
Section: Basic Monitoringmentioning
confidence: 99%
“…In addition, the Alfred I. duPont Hospital for Children/Nemours Research Lung Center Institutional Animal Care and Use Committee approved this study. Our earlier research indicated that the original and modified Isolettes had comparable temperature, relative humidity, O 2 and CO 2 response times during environmental start-up and maintenance experiments for either Hx or control conditions [15,16] . Environmental control is maintained by an integrated forced air circulation system.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, data are limited regarding the long-term effects of an N 2 -free Hx environment on early mammalian growth and development. In order to address these issues, we modified two Hill-Rom Air-Shields Isolette (Hatboro, Pa., USA) infant incubators to deliver Hx respiratory gas mixtures and provide thermal stability for infants in the NICU [15] .…”
mentioning
confidence: 99%